The Role of English in Global Business Communication - Bhat, Prem Singh (The Management Review, 2026)
English is gaining ascendancy as an important language of communication in the business world across the globe. In the globalized world, English has become essential for transactions to take place among organizations, entrepreneurs and even international markets and businesses. In this paper, it is proposed that English proficiency affects the context of business communication especially on entrepreneurs and how it is utilized in developing a connection between international and local businesses. Both descriptive and qualitative methodologies are employed in the paper to show the importance of English proficiency as a phenomenon in improving the professionalism and work opportunities of the world market.